Central and total obesity in middle aged men and women in relation to lifetime socioeconomic status: evidence from a national birth cohort. Issue 10 (22nd October 2003) - Langenberg, C; Hardy, R; Kuh, D; Brunner, E; Wadsworth, M
Abstract : Study objective: To investigate the influence of social class in childhood, young adulthood and middle age, and intergenerational mobility, on adult central and total obesity. Design: Prospective, population based, birth cohort study. Participants and Setting: 1472 men and 1563 women born in 1946 in England, Scotland, and Wales. Outcome measures: Waist-hip ratio, waist-height ratio, waist circumference, and body mass index at age 53 years. Main results: Father's social class at participant's age 4 years was inversely associated with adult central and total obesity at age 53 years in men and women. For example, the mean difference of waist-hip ratio (95% confidence intervals) between father's professional social class I and unskilled manual social class V was 2.6% (0.7 to 4.6) for men and 2.5% (0.5 to 4.4) for women. The effect of father's social class remained after adjustment for participant's own social class in young adulthood and middle age. Both adult social classes were inversely related to obesity among women, but not men, after adjustment for childhood circumstances. Upwardly mobile men and women were less obese than participants remaining in their father's social class and their levels of obesity tended to be between the class they left and the class they joined. Conclusions: The effect of social class on adult obesity differed according to the stage in the life course at which social class was measured, and gender. Childhood circumstances had enduring influences on adult obesity, although our results on intergenerational mobility indicate potential reversibility of early life disadvantage.